PERLINDUNGAN HAK ULAYAT WARGA DEGEUWO TERHADAP PENAMBANGAN ILEGAL - Stenley Ludya Liap (to-ra, 2017)
The protection of the Ulayat Right from illegal mining is a form of government responsibility in recognizing and protecting the rights of indigenous peoples to the land they control. However, sometimes customary lands owned by local indigenous peoples in certain areas containing certain natural resources are targeted by outside miners. In Indonesia, illegal mining cases that occur include illegal mining in Degeuwo area where the ulayat land has a high gold content. External entrepreneurs who conduct illegal mining in the area are alleged to have made a closed deal to some local indigenous people and use the apparatus to protect the mining process there which resulted in internal conflicts and even murder cases. This article concludes that Indonesian law has recognized and protected customary rights of indigenous peoples governed by the Land Law, Mining Law, Criminal Code and other related rules. Keywords: Perlindungan Hak Ulayat